2017
DOI: 10.1002/fsn3.555
|View full text |Cite
|
Sign up to set email alerts
|

Preservative effects of some selected spice oleoresins to stabilize the sunflower oil in comparison to tertiary butylhydroquinone

Abstract: DPPH (1, 1‐Diphenyl‐2‐Picrylhydrazyl) radical scavenging activity was performed to find out the antioxidant activity (AA) of all the antioxidants used at a concentration of 5, 10, and 15 μl/ml. Effect of spice oleoresins (clove, black pepper, and ginger) (200 ppm) and TBHQ (200 ppm) were incorporated in stabilizing refined, bleached, and deodorized (RBD) sunflower oil heating at frying temperature (170°C) and during accelerated oxidation storage (70°C) was studied in comparison to Tert‐Butylhydroquinone (TBHQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Their results revealed that FFA content and PV increment were significantly low in spices incorporated oil samples compared to that pure oil samples. Similar results were found that Pradhananga and Manandhar (2018) for sunflower oil. According to their results, FFA and PV of sunflower oil were found to be increasing with the heating time and reported that the FFA level and PV can be decreased by adding TBHQ.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Their results revealed that FFA content and PV increment were significantly low in spices incorporated oil samples compared to that pure oil samples. Similar results were found that Pradhananga and Manandhar (2018) for sunflower oil. According to their results, FFA and PV of sunflower oil were found to be increasing with the heating time and reported that the FFA level and PV can be decreased by adding TBHQ.…”
Section: Discussionsupporting
confidence: 89%
“…According to their results, PV and FFA levels were significantly decreased in treat oil with cinnamon extract. Pradhananga and Manandhar (2018) reported that PV and FFA levels of sunflower oil were decreased after the incorporation of spices oleoresins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported that corn oil with thyme extract showed the least peroxide value during deep frying. A similar study was conducted by Pradhananga and Manandhar [11]. They have also reported that FFA and PV of sunflower oil were found to be increasing with the heating time and reported that FFA and PV can be decreased by adding TBHQ.…”
Section: Thermal Stability Of Flavored Oilsupporting
confidence: 64%
“…To analyze the antioxidant activity of coconut oil, the method described by Pradhananga and Manandhar [ 11 ] was used with slight modifications. Thus, 500 μ l aliquot of each concentration was mixed with 2500 μ l of DPPH working solution in screw-capped 4 ml micro test tubes covered with an Al foil.…”
Section: Methodsmentioning
confidence: 99%